PENGOLAHAN AIR LIMBAH RUMAH SAKIT MENGGUNAKAN HORIZONTAL SUBSURFACE FLOW CONSTRUCTED WETLAND - Gede H. Cahyana; Annisha Nur Aulia (Universitas Kebangsaan, 2019)
Activated sludge is a wastewater treatment reactor widely applied for hospital. The reactor requires a mechanical aerator as a source of oxygen. At the same time, Subsurface Flow Constructed Wetland is rarely used. Both types of reactors utilize microbes in reducing pollutants of wastewater. The role of microbes in activated sludge is taken over by microbes that grow in the root zone of Typha latifolia and Vetiver sp. Two laboratory scale reactors were made to get serial data on the performance of the two plants in treating hospital wastewater. The result, the removal efficiency of COD on Q1 = 0.13 l/h and COD on Q2 = 0.43 l/h for Typha latifolia plants were 87.71% and 67.61%. On Vetiver sp. plants were 90,07% and 68,32%. The removal efficiency of BOD5 on Q1 = 0.13 l/h and Q2 = 0.43 l/h for Typha latifolia plants were 90.00% and 71.7%. On Vetiver sp. plants were 91.69% and 73.29%. The efficiency of Total Kjeldahl Nitrogen removal (TKN) Q1 = 0.13 l/h and Q2 = 0.43 l/h for Typha latifolia plants were 91.27% and 61.54%, whereas in Vetiver sp. plants were 92.01% and 62.68%. Horizontal Subsurface Flow Constructed Wetland is capable and feasible for hospital wastewater treatment. Keywords: Subsurface Flow Constructed Wetland, Typha latifolia, Vetiver sp.